IDNLearn.com is your go-to resource for finding expert answers and community support. Our community is ready to provide in-depth answers and practical solutions to any questions you may have.
Sagot :
Sure, let's solve the system of equations step-by-step.
The given system of equations is:
1. [tex]\(4x + 9y - 5xy = 0\)[/tex]
2. [tex]\(\frac{x + 2y}{xy} = 2\)[/tex]
First, let's rewrite the second equation to make it easier to handle algebraically:
[tex]\[ \frac{x + 2y}{xy} = 2 \][/tex]
Multiplying both sides by [tex]\(xy\)[/tex] to clear the fraction, we get:
[tex]\[ x + 2y = 2xy \][/tex]
Rearranging this equation, we get:
[tex]\[ x + 2y - 2xy = 0 \quad \text{(Equation 3)} \][/tex]
Now we have the following system of equations:
1. [tex]\(4x + 9y - 5xy = 0\)[/tex]
2. [tex]\(x + 2y - 2xy = 0\)[/tex]
Next, let's solve the second equation for one of the variables, say [tex]\(x\)[/tex]:
From Equation 3:
[tex]\[ x + 2y - 2xy = 0 \][/tex]
Factoring [tex]\(x\)[/tex] out from the terms involving [tex]\(x\)[/tex], we get:
[tex]\[ x(1 - 2y) = -2y \][/tex]
Assuming [tex]\(1 - 2y \neq 0\)[/tex], we solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{-2y}{1 - 2y} \][/tex]
Now substitute [tex]\(x\)[/tex] from this expression into the first equation.
Substitute [tex]\(x = \frac{-2y}{1 - 2y}\)[/tex] into Equation 1:
[tex]\[ 4 \left(\frac{-2y}{1 - 2y}\right) + 9y - 5 \left(\frac{-2y}{1 - 2y}\right)y = 0 \][/tex]
Simplifying each term separately:
[tex]\[ 4 \left(\frac{-2y}{1 - 2y}\right) = \frac{-8y}{1 - 2y} \][/tex]
[tex]\[ -5 \left(\frac{-2y}{1 - 2y}\right)y = \frac{10y^2}{1 - 2y} \][/tex]
Thus the equation becomes:
[tex]\[ \frac{-8y + 9y(1 - 2y) + 10y^2}{1 - 2y} = 0 \][/tex]
Simplifying the numerator:
[tex]\[ -8y + 9y - 18y^2 + 10y^2 = 0 \][/tex]
Combining like terms:
[tex]\[ y - 8y^2 = 0 \][/tex]
Factoring out [tex]\(y\)[/tex]:
[tex]\[ y(1 - 8y) = 0 \][/tex]
This gives us two possible solutions for [tex]\(y\)[/tex]:
[tex]\[ y = 0 \quad \text{or} \quad 1 - 8y = 0 \][/tex]
Solving [tex]\(1 - 8y = 0\)[/tex], we get:
[tex]\[ y = \frac{1}{8} \][/tex]
For [tex]\(y = 0\)[/tex], substituting in the second equation:
[tex]\[ x + 2(0) - 2x(0) = 0 \implies x = 0 \][/tex]
However, [tex]\(x = 0\)[/tex] does not satisfy the first equation, so this solution is discarded.
For [tex]\(y = \frac{1}{8}\)[/tex]:
Substituting [tex]\(y = \frac{1}{8}\)[/tex] back into [tex]\(x = \frac{-2y}{1 - 2y}\)[/tex]:
[tex]\[ x = \frac{-2(\frac{1}{8})}{1 - 2(\frac{1}{8})} = \frac{-\frac{1}{4}}{1 - \frac{1}{4}} = \frac{-\frac{1}{4}}{\frac{3}{4}} = -\frac{1}{3} \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ x = -\frac{1}{3} \quad \text{and} \quad y = \frac{1}{8} \][/tex]
So the solution is [tex]\((- \frac{1}{3}, \frac{1}{8})\)[/tex].
The given system of equations is:
1. [tex]\(4x + 9y - 5xy = 0\)[/tex]
2. [tex]\(\frac{x + 2y}{xy} = 2\)[/tex]
First, let's rewrite the second equation to make it easier to handle algebraically:
[tex]\[ \frac{x + 2y}{xy} = 2 \][/tex]
Multiplying both sides by [tex]\(xy\)[/tex] to clear the fraction, we get:
[tex]\[ x + 2y = 2xy \][/tex]
Rearranging this equation, we get:
[tex]\[ x + 2y - 2xy = 0 \quad \text{(Equation 3)} \][/tex]
Now we have the following system of equations:
1. [tex]\(4x + 9y - 5xy = 0\)[/tex]
2. [tex]\(x + 2y - 2xy = 0\)[/tex]
Next, let's solve the second equation for one of the variables, say [tex]\(x\)[/tex]:
From Equation 3:
[tex]\[ x + 2y - 2xy = 0 \][/tex]
Factoring [tex]\(x\)[/tex] out from the terms involving [tex]\(x\)[/tex], we get:
[tex]\[ x(1 - 2y) = -2y \][/tex]
Assuming [tex]\(1 - 2y \neq 0\)[/tex], we solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{-2y}{1 - 2y} \][/tex]
Now substitute [tex]\(x\)[/tex] from this expression into the first equation.
Substitute [tex]\(x = \frac{-2y}{1 - 2y}\)[/tex] into Equation 1:
[tex]\[ 4 \left(\frac{-2y}{1 - 2y}\right) + 9y - 5 \left(\frac{-2y}{1 - 2y}\right)y = 0 \][/tex]
Simplifying each term separately:
[tex]\[ 4 \left(\frac{-2y}{1 - 2y}\right) = \frac{-8y}{1 - 2y} \][/tex]
[tex]\[ -5 \left(\frac{-2y}{1 - 2y}\right)y = \frac{10y^2}{1 - 2y} \][/tex]
Thus the equation becomes:
[tex]\[ \frac{-8y + 9y(1 - 2y) + 10y^2}{1 - 2y} = 0 \][/tex]
Simplifying the numerator:
[tex]\[ -8y + 9y - 18y^2 + 10y^2 = 0 \][/tex]
Combining like terms:
[tex]\[ y - 8y^2 = 0 \][/tex]
Factoring out [tex]\(y\)[/tex]:
[tex]\[ y(1 - 8y) = 0 \][/tex]
This gives us two possible solutions for [tex]\(y\)[/tex]:
[tex]\[ y = 0 \quad \text{or} \quad 1 - 8y = 0 \][/tex]
Solving [tex]\(1 - 8y = 0\)[/tex], we get:
[tex]\[ y = \frac{1}{8} \][/tex]
For [tex]\(y = 0\)[/tex], substituting in the second equation:
[tex]\[ x + 2(0) - 2x(0) = 0 \implies x = 0 \][/tex]
However, [tex]\(x = 0\)[/tex] does not satisfy the first equation, so this solution is discarded.
For [tex]\(y = \frac{1}{8}\)[/tex]:
Substituting [tex]\(y = \frac{1}{8}\)[/tex] back into [tex]\(x = \frac{-2y}{1 - 2y}\)[/tex]:
[tex]\[ x = \frac{-2(\frac{1}{8})}{1 - 2(\frac{1}{8})} = \frac{-\frac{1}{4}}{1 - \frac{1}{4}} = \frac{-\frac{1}{4}}{\frac{3}{4}} = -\frac{1}{3} \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ x = -\frac{1}{3} \quad \text{and} \quad y = \frac{1}{8} \][/tex]
So the solution is [tex]\((- \frac{1}{3}, \frac{1}{8})\)[/tex].
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.